Prediction of Moderate to Severe Obstructive Sleep Apnea Using Neck Computed Tomography With Computational Fluid Dynamics Study - Chung, Wei-Sheng; Chung, Sunny (Frontiers in Medicine, 2022)
Background:Moderate to severe obstructive sleep apnea (OSA) is associated with cardiovascular disease. Polysomnography is time intensive and difficult to access for diagnosis of OSA. Neck computed tomography (CT) provides upper airway delineation but not diagnostic criteria for moderate to severe OSA. We explored neck CT with computational fluid dynamics (CFD) study for airway pressure and airflow velocity to predict moderate to severe OSA. Methods:Enrolled from February 1, 2020, to June 30, 2021, patients with OSA with overnight oxygen desaturation (sPO2 < 90%) received awake neck CT with a CFD study of their airway pressure and airflow velocity. CTL12 and CTL34 were defined as airflow velocity < 3 m/s and ≥ 3 m/s, respectively, and airway pressure < 10 pa and ≥ 10 pa, respectively, in the narrowest upper airway. Results:Sixty-two patients were included; 12 and 50 patients had mild OSA and moderate to severe OSA, respectively. Most (85.5%) neck CT examinations with CFD study presented CTL34. Patients with CTL34 had a lower minimum sPO2 in the supine position (78.4% vs 88.1%, P = 0.004) and longer duration of sPO2 < 90% at overnight oximetry (33.9 min vs 1.9 min, P = 0.001) than those with CTL12. The values of the area under the receiver operating characteristic curves of airway pressure and of airflow velocity at the narrowest upper airway were 0.788 and 0.733, respectively. Conclusions:Neck CT with CFD study of airway pressure and airflow velocity may provide a quick prediction of moderate to severe OSA.